Congenital Ostium Secundum Atrial Septal Defect with Mitral Valve Prolapse and Mitral Regurgitation – A Case Report and Review of Literature - Hossain, Md Aslam; Joshi, Dharmendra; Acharya, Mayank; Morshed, Tareq; Khan, Omar Sadeque; Sunny, Samir Azam; Rahman, Md Mukhlesur (University Heart Journal, 2018)
Mitral regurgitation (MR) associated with secundum Atrial Septal Defect (ASD) is not widely recognized but the association is not unusual. MR has been found in less than 10% of adults with large ASD which is mainly caused by mitral valve prolapse (MVP). We are reporting a case of congenital ostium secundum ASD with MVP associated with MR, review the clinical relevance of this association, and discuss the related literature. Our patient has shown dramatic improvement in symptoms and signs after ASD closure with mitral valve replacement along with improvement in tricuspid regurgitation. More general awareness of this association will further help the surgeon for better management of the patient with this rather unusual combination of lesions. University Heart Journal Vol. 12, No. 2, July 2016; 91-94